The Influence of Service Quality And Perceived Value on Customer Loyalty in Toraja Cultural Sites - Tandipayuk, Grace Permatasari; Kakeeto-Aelen, Terry (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
Indonesia has been blessed with cultural, natural, and historical resources, all of which offer Indonesia the opportunity to become one of the key tourist destinations in the world. Toraja, as one of the top tourist destinations in Indonesia, must be able to deal with increasing demands regarding service quality in the destination, attract tourists, and encourage repeat visits of tourists. The purpose of this study was to investigate the service quality levels in the Toraja cultural heritage sites and to establish how these might affect the perceived value of the tourists and their loyalty towards the service. The SERVQUAL model was used to measure service quality in the Toraja cultural heritage sites. A mixed methodology was used in this research. Quantitative methods used to collect data from local and foreign tourists visiting the sites during the data collection period. Qualitative methods used to collect data through semi-structured interviews. The results show service quality had a significant influence on tourists’ perceived value and customer loyalty in the cultural heritage sites of Toraja. The service quality dimensions that had a significant influence on tourists’ perceived value, and customer loyalty was responsiveness, empathy, and reliability. Tangibles and assurance did not have a significant influence on tourists’ perceived value and customer loyalty